Identification of a New Integration Site and Study on Site-Specific Integration in CHO-K1 Cells - Hong Liu; Wei Zhang; Liping Xie; Youjia Hu (MDPI AG, 2023)
Site-specific integration is an important approach used to address the problem of unstable cell lines in industry. In this study, we observed a reduction in the gene copy number and antibody production in a CHOK1 cell line BA03 capable of high antibody expression. We identified a new integration site named locus 7 in the intron region of the parva gene through sequencing, FISH, and genome walking. We demonstrate that the integration of the exogenous gene at this locus does not affect the transcription of the parva and, therefore, has a minimal impact on cell growth. We designed sgRNA and donor vectors to integrate the etanercept-coding gene into locus 7 and obtained a cell line, SSI-4. We performed a passaged stability study on SSI-4 and proved the possibility of the stable, site-specific integration of exogenous genes at this locus in terms of integration site, copy number, expression level, and cell growth. In summary, our study has identified a new integration site suitable for site-specific integration, which lays the foundation for the subsequent development of site-specific integration cell lines.